Conducting a real-world study of Tumor Necrosis factor-alpha inhibitors-induced Systemic Lupus Erythematosus based on the FAERS database - Mengjiao He; Jiale Yang; Simin Yan; Qing Shu; Peng Cheng Liu (Scientific Reports)
Abstract This study characterized the risk and characteristics of tumor necrosis factor-α (TNF-α) inhibitors-induced systemic lupus erythematosus (SLE) in a mass medication population based on the FAERS database. Using the Standardized MedDRA Query (SMQ), adverse drug reaction (ADR) reports related to SLE of infliximab, adalimumab, etanercept, golimumab, and certolizumab pegol were collected from the FAERS database starting from the data retrieval quarter up to the fourth quarter of 2023. Signal detection was performed using the Reporting Odds Ratio (ROR) method and the Bayesian Confidence Interval Propagation Neural Network (BCPNN) method to comprehensively explore the risks. Subgroup analyses were conducted for different genders and age groups to provide a detailed insight into the risks. A total of 12,080 reports of TNF-α inhibitors-induced SLE have been collected, with over 90% of the reports showing serious outcomes, including life-threatening, death and others. Notably, deaths were prominently associated with certolizumab pegol and etanercept. Regarding time to onset, the median time to onset after drug use was over 7 months for infliximab, adalimumab, and etanercept, while for golimumab and certolizumab pegol, the median time to onset was around 2 months post-treatment. At the SMQ level, all five TNF-α inhibitors showed statistically significant signals in the overall population, with the strength of association ranked as infliximab > adalimumab > certolizumab pegol > golimumab > etanercept. In terms of PT level, apart from signals related to lupus-like syndrome, systemic lupus erythematosus, and systemic lupus erythematosus rash, notable findings include the higher signal intensity of SLE arthritis in the subgroup of male with adalimumab, lupus nephritis risk associated with etanercept in the children (0–14 years) subgroup, and rare and severe occurrences of pericarditis lupus and lupus pleurisy induced by infliximab. This study utilized large-scale real-world data to reveal varying degrees of SLE associated with five TNF-α inhibitors and characterized specific risk signals of concern across gender and age subgroups. This suggests that different TNF-α inhibitors should be continuously monitored for SLE-induced complications in clinical practice, and that appropriate drug management should be carried out for different patients. Further research is necessary to validate our findings.